A new linguistic computation method under fuzzy environment - Tarmudi, Zamali; Md. Tap, Abu Osman; Abdullah, Mohd Lazim (2009)
In this paper, a computation method is proposed using fully linguistic variables in conflicting bifuzzy sets. The linguistic terms was defined briefly associated with the triangular fuzzy number and labeling system in early stages. Then, the conflicting negation operator was introduced and employs the bifuzzy approaches to derive the linguistic equilibrium judgment for evaluating purposes. Finally, a hypothetical example is given to apply our proposed method. The results show that the method is highly beneficial and offers a new dimension technique for problem solving under fuzzy environment.